Le référendum du 23 juin 2016 en Écosse : entre deux unions - Edwige Camp-Pietrain (Revue Française de Civilisation Britannique)
On June 23rd the Scots voted to remain in the UE contrary to the majority of voters in the UK. This discrepancy was to be expected as most senior politicians in Scotland had campaigned for the EU regarded as an asset and not as a threat. The ruling SNP has seized the opportunity to put a second referendum on Scotland's independence on the agenda. The Scots might thus have to choose between two unions -the EU and the UK- in spite of the prevailing uncertainty.